1998
DOI: 10.1046/j.1365-201x.1998.0248f.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrity and metabolism of human ileal mucosa in vitro in the Ussing chamber

Abstract: The Ussing chamber is increasingly being used for in vitro studies of human intestinal mucosa, but little attention has been paid to the viability of specimens over time. Ninety-one mucosal specimens from the ileum in 19 patients operated on for colonic cancer were studied in regard to intestinal barrier function, metabolism, electrophysiology and histology during 360 min of incubation in Ussing chambers. Steady-state permeability to 51Cr-EDTA was maintained for 120 min. Mucosal ATP and lactate levels were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…They have also shown that the permeability of the water-soluble substance mannitol was time-dependently increased, although only by a small degree. The human ileum incubated in Ussing chambers for more than 2 h has reportedly shown that the permeability to 51 Cr-EDTA (Mr 360) was increased in parallel with epithelial lifting and sloughing, although the magnitude of the increase was moderate (14). These reports support our proposal that the subepithelial lamina propria/submucosa of the small intestine constitute a non-epithelial diffusion barrier to water-soluble molecules (including NaCl).…”
Section: Discussionsupporting
confidence: 79%
“…They have also shown that the permeability of the water-soluble substance mannitol was time-dependently increased, although only by a small degree. The human ileum incubated in Ussing chambers for more than 2 h has reportedly shown that the permeability to 51 Cr-EDTA (Mr 360) was increased in parallel with epithelial lifting and sloughing, although the magnitude of the increase was moderate (14). These reports support our proposal that the subepithelial lamina propria/submucosa of the small intestine constitute a non-epithelial diffusion barrier to water-soluble molecules (including NaCl).…”
Section: Discussionsupporting
confidence: 79%
“…A four electrode system was used as previously described. 20 One pair of Ag/ Ag-electrodes (Ref 201, Radiometer, Copenhagen, Denmark) with 3 M NaCl/2% agar bridges was used for measurements of PD and one pair of platinum electrodes for current passage. Transepithelial potential difference, Isc and TER were obtained as described by Karlsson et al 21 The electrodes were coupled to an external six channel electronic unit with a voltage controlled current source.…”
Section: Ussing Chamber Experimentsmentioning
confidence: 99%
“…In previous studies of human intestinal mucosa maintained in Ussing chambers, I sc and G t were stable for at least 2 h and the epithelial surface remained histologically intact for at least 2.5 h (Larsen et al, 2001;Soderholm et al, 1998). Because epithelial degradation and edema occur after several hours of incubation (Figure 2 and (Larsen et al, 2001;Soderholm et al, 1998), experiments in the Ussing chamber were limited to 2 to 3 h. Glucose-stimulated Na + absorption at the end of the incubation period demonstrated that the JPP was functionally intact (Larsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%